2015
DOI: 10.1007/s40596-015-0308-y
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatrists’ and Psychiatry Residents’ Attitudes Toward Transgender People

Abstract: These data evoke optimism regarding psychiatrists' and psychiatry residents' attitudes toward transgender individuals. Additional larger-scale studies comparing this medical specialty group with other specialty groups will further elucidate factors that modify physician attitudes toward this patient population. These findings may contribute to the development of educational strategies to ensure that the transgender population receives medical treatment without stigma or attitudinal compromise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 15 publications
3
36
0
1
Order By: Relevance
“…The three studies reported here mirror previous research (e.g., Ali et al, 2016;Bowers et al, 2015;Nisley 2010) in finding more negative (on the GTS-RA) or less positive (on the CATTS) attitudes towards transgender people amongst cisgender men as compared to cisgender women within three Australian samples of cisgender psychologists and trainees.…”
Section: Discussionsupporting
confidence: 86%
“…The three studies reported here mirror previous research (e.g., Ali et al, 2016;Bowers et al, 2015;Nisley 2010) in finding more negative (on the GTS-RA) or less positive (on the CATTS) attitudes towards transgender people amongst cisgender men as compared to cisgender women within three Australian samples of cisgender psychologists and trainees.…”
Section: Discussionsupporting
confidence: 86%
“…This may be because the latter is rather blunt in the wording of its items, and the former includes both attitudinal and knowledge items. The issue of measures focusing on attitudes towards trans people being too blunt has also been raised by Ali et al (2016), whose participants suggested that the Genderism and Transphobia Scale (Hill & Willoughby, 2005) uses "unnecessarily inflammatory language" (p. 271). Concerns about the Genderism and Transphobia Scale led Riggs, Webber and Fell (2012) to adapt the scale in ways similar to the adaptions applied to the CATTS and ATTIS in the present study, producing factors that were argued to be relevant to the Australian context.…”
Section: Discussionmentioning
confidence: 99%
“…Bowers et al also found that participants with more training about trans issues and the needs of trans clients were also more likely to have positive attitudes towards trans students. Similarly, a study of psychiatrists conducted by Ali, Fleisher and Erickson (2016) and a study of counselling professionals conducted by Claman (2005) found that having previously worked with trans clients predicted more positive attitudes. Conversely, a study of masters and doctoral student counsellors and counselling psychologists found greater expression of anti-trans attitudes amongst those who had less training and experience with trans clients (Nisley, 2010).…”
Section: Attitudes Towards Trans Peoplementioning
confidence: 96%
“…Both the variation in transgender presentation and the growing size of this population highlight the need for healthcare professionals to approach gender identity with fewer assumptions and an open perspective regarding patient needs [4]. However, in both the general population and in medical healthcare, stigma continues to exist against transgender individuals.…”
mentioning
confidence: 99%
“…However, in both the general population and in medical healthcare, stigma continues to exist against transgender individuals. In the general USA population, a 2013 sample of over 2000 heterosexual adults noted significantly less favorable self-reported attitudes towards transgender people than attitudes towards gay men, lesbians, and bisexuals [4]. Although public awareness of transgender individuals may be increasing due to popular culture transgender individuals and political discussions, the ability of transgender individuals to integrate in society at large, such as navigating bathroom laws or serving in the US military, remains a topic fraught with contemporary controversy [2].…”
mentioning
confidence: 99%